Elementary School Buildings with the Direction of Sustainability Awareness Construction - Kayihan, Kutlu Sevinc; Tonuk, Seda (GAZI UNIV, 2011)
Sustainable design approach which is proposed as a solution to environmental problems caused by architectural activities proposes different solutions to various conditions and stipulates to consider such a wide spectrum which simultaneously consists of environmental, economic, social and cultural subjects at design process. Sustainable architectural design is a design approach focusing on the future of the earth as main idea, not to the human comfort. In this context, sustainability will be possible with individuals of societies reaching a conscious level which can protect future generations' right to life. In this context, the success of sustainability efforts will be possible to reach a level of consciousness of individuals can protect the right to life of future generations. An educational process focused on the topic starting from an early age should establish the most important step. Therefore, elementary schools that serve to the age group of 6-14 users, as buildings can be taught to young generations aware of sustainability with education have a great importance and potential compared to other building types. This requires an intensive training process which will be starting from early ages. Elementary school buildings serving users in the age group of 6-14 years facilities build awareness of sustainability has a great significance and potential compared to other building types. In this context, the subject area of this study constitutes of social design criteria of elementary school buildings which will be designed in light of sustainable design approach. In the first part of the study main headings of the total sustainability criteria of the elementary school buildings are formulated with environmental, economic and social design criteria headings. Then sub-criteria of the each main heading is classified and in this context, the schematic presentation of the sustainable design support model for elementary school buildings is attempted to be created. Because of the very comprehensive subject, social design criteria were selected as the subject of the study. Social design criteria subject for the elementary school buildings is dealt in the scope of these headings; *Social integration through design, *Being sustainability education tool for the users and society, *Reflection of the social values through design, *Improving educational performance through design The reflections of these headings to the outdoor space and building design were evaluated. Especially design criteria providing elementary school buildings to be an educational tool on sustainability both for the students and the habitants of the area were thoroughly discussed.
Keywords: sustainable elementary school buildings; sustainable education; sustainable educational spaces; Engineering